Carotid Dissection and Isolated Paralysis of Ipsilateral Half Tongue: Clinical Cases. (19th December 2020) - Agbotsou, Komi Igneza; Kombate, Damelan; Mehri, Christopher; Apetse, Kossivi; Bakpatina-Batako, Kpalma Duga; Guerrier, Olivier; Beschet, Albert; Blanc Lasserre, Karine; Breynaert, Ludovic; Chan, Victor
Abstract : Objective . We report two cases of carotid dissection revealed by isolated paralysis of the ipsilateral half tongue. Observations . First patient, 52 years old, with no particular medical or surgical history, presented with isolated paralysis of the left half tongue preceded by two weeks of moderate-intensity cervicalgia and having been the subject to cervical manipulation. MRI revealed dissection of the left internal carotid artery in its prepetrous portion. The evolution after 6 weeks of platelet aggregating inhibitors treatment was favorable. The second patient, 74 years old, with no particular medical or chirurgical history, presented with a sudden onset of paralysis of the left half tongue preceded by unusual headaches associated with neck pain. Brain MRI showed aneurysmal ectasia of the left internal carotid with parietal irregularity suggestive of carotid dissection. The evolution after four weeks of treatment with anticoagulant was favorable. Conclusion . Carotid dissection revealed by isolated paralysis of the half tongue is rare. It is generally of good prognosis. However, in paralysis of half tongue, it must be urgently sought and treated to reduce the risk of a transient or constituted ischemic accident.